Cannabinoids for the Treatment of Dermatologic Conditions - Torunn E. Sivesind; Jalal Maghfour; Hope Rietcheck; Kevin Kamel; Ali S. Malik; Robert P. Dellavalle (Elsevier, 2022)
In recent years, cannabinoid (CB) products have gained popularity among the public. The anti-inflammatory properties of CBs have piqued the interest of researchers and clinicians because they represent promising avenues for the treatment of autoimmune and inflammatory skin disorders that may be refractory to conventional therapy. The objective of this study was to review the existing literature regarding CBs for dermatologic conditions. A primary literature search was conducted in October 2020, using the PubMed and Embase databases, for all articles published from 1965 to October 2020. Review articles, studies using animal models, and nondermatologic and pharmacologic studies were excluded. From 248 nonduplicated studies, 26 articles were included. There were 13 articles on systemic CBs and 14 reports on topical CBs. Selective CB receptor type 2 agonists were found to be effective in treating diffuse cutaneous systemic sclerosis and dermatomyositis. Dronabinol showed efficacy for trichotillomania. Sublingual cannabidiol and Δ-9-tetrahydrocannabinol were successful in treating the pain associated with epidermolysis bullosa. Available evidence suggests that CBs may be effective for the treatment of various inflammatory skin disorders. Although promising, additional research is necessary to evaluate efficacy and to determine dosing, safety, and long-term treatment guidelines.